A cutting-edge new framework for the pain management in children: nanotechnology - Starcea, Iuliana Magdalena; Lupu, Ancuta; Nistor, Ana Maria; Mocanu, Maria Adriana; Bogos, Roxana Alexandra; Azoicai, Alice; Cira, Diana; Beldie, Madalina; Lupu, Vasile Valeriu; Morariu, Ionela Daniela; Munteanu, Valentin; Tepordei, Razvan Tudor; et al. (Frontiers in Molecular Neuroscience, 2024)
Pain is a subjective concept which is ever-present in the medical field. Health professionals are confronted with a variety of pain types and sources, as well as the challenge of managing a patient with acute or chronic suffering. An even bigger challenge is presented in the pediatric population, which often cannot quantify pain in a numerical scale like adults. Infants and small children especially show their discomfort through behavioral and physiological indicators, leaving the health provider with the task of rating the pain. Depending on the pathophysiology of it, pain can be classified as neuropathic or nociceptive, with the first being defined by an irregular signal processing in the nervous system and the second appearing in cases of direct tissue damage or prolonged contact with a certain stimulant. The approach is generally either pharmacological or non-pharmacological and it can vary from using NSAIDs, local anesthetics, opiates to physical and psychological routes. Unfortunately, some pathologies involve either intense or chronic pain that cannot be managed with traditional methods. Recent studies have involved nanoparticles with special characteristics such as small dimension and large surface area that can facilitate carrying treatments to tissues and even offer intrinsic analgesic properties. Pediatrics has benefited significantly from the application of nanotechnology, which has enabled the development of novel strategies for drug delivery, disease diagnosis, and tissue engineering. This narrative review aims to evaluate the role of nanotechnology in current pain therapy, with emphasis on pain in children.